Chemical exposure in garage workers and related health risks on the biochemical levels: A comparative study in Harar town, eastern Ethiopia. (April 2019) - Ataro, Zerihun; Geremew, Abraham; Urgessa, Fekadu
Objectives: Occupational exposure to chemicals causes a wide range of biological effects depending on the level and duration of exposure. The current study is intended to determine the differences in biochemical levels among garage workers compared with occupationally nonexposed participants in Harar town, eastern Ethiopia. Methods: A comparative cross-sectional study was conducted in Harar town, eastern Ethiopia. Thirty (30) garage workers were selected and compared with 30 age- and sex-matched control group of teachers and students. Demographic and occupational data were collected using a structured questionnaire by trained data collector. Biochemical levels were measured by automated clinical chemistry analyzer (Autolab 18, Boehringer-Mannheim Diagnostics, the United States). Data were analyzed using STATA Version 13. Results: All of the included garage workers were male. A statistically significant increase were found in alanine aminotransferase (35.60 ± 7.93 vs 19.17 ± 0.91 U/L; P value = 0.0440), aspartate aminotransferase (47.23 ± 4.89 vs 27.03 ± 1.13 U/L; P value = 0.0002), total protein (85.83 ± 1.16 vs 76.40 ± 0.86 g/l; P value < 0.0001), uric acid (7.34 ± 0.29 vs 5.19 ± 0.21 mg/dl; P value < 0.0001), glucose (85.13 ± 3.92 vs 75.60 ± 2.40 mg/dl; P value = 0.0425); total cholesterol (199.40 ± 13.11 vs 140.37 ± 3.81 mg/dl; P value = 0.0001) and triglyceride (143.40 ± 5.79 vs 110.60 ± 8.98 mg/dl; P value = 0.0033) in garage workers compared with control group. On the contrary, a statistically significant decrease were found in albumin (39.37 ± 1.78 vs 46.37 ± 0.56 g/l; P value = 0.0004) and urea (21.63 ± 1.04 vs 27.60 ± 1.69 mg/dl; P value = 0.0039) among garage workers compared with the control group. Conclusion: Our finding indicates that working in the garage changes most of the biochemical levels. Therefore, appropriate and effective safety measures need to be implemented to prevent possible chemical exposure during routine work.